Catechol redox couple functionalized metal-organic framework UiO-66-NH2 as an efficient catalyst for chromium ion sensor in water samples. (10th November 2022) - Ranjith Kumar, Deivasigamani; Karthik, Raj; Dhakal, Ganesh; Nguyen, Van Quang; Lee, Jintae; Shim, Jae-Jin
Abstract: Hexavalent chromium (Cr 6+ ) is a major toxic pollutant than the trivalent (Cr 3+ ) in water, which is challenging for selective Cr 6+ detection in an acidic medium. Zirconium-cluster (Zr6 ) metal-organic frameworks (MOFs) are highly stable in acid medium, and their three-dimensional structures enable facile access to target analytes. However, non-electroactive metals and linkers within MOFs limit their electrochemical applications. Therefore, the purpose of the present study is an innovative diazotization of redox-active functional moiety on the non-electroactive MOF to electroactive MOF for electrocatalytic applications. Present work, post-synthetically diazotized UiO-66-NH2 MOF with redox-active catechol form UiO-66-NN-φ(OH)2 . Phenolic groups in as-prepared UiO-66-NN-φ(OH)2 were revealed as excellent redox couple that was effectively used as an electrocatalytic Cr 6+ sensor. The pKa (Brønsted acidities) of the Zr-η3 -OH and functional catechol were estimated. To improve redox current, electrochemically reduced graphene oxide (ERGO) was used as a substrate for UiO-66-NN-φ(OH)2 MOF with the surface coverage (τ) of 6.63 × 10 −10  mol cm −2 . In contrast, the τ value of UiO-66-NN-φ(OH)2 /glassy carbon (GC) electrode was 2.12 × 10 −11  mol cm −2 . The temperature effect on the redox chemistry of UiO-66-NN-φ(OH)2 @ERGO/GC C–OH and Cr 6+ was examined. The UiO-66-NN-φ(OH)2 @ERGO/GC electrode operates in a wide Cr 6+ concentration range (0.062–962 μM) with excellent sensitivity (0.211 μA μM −1 ), a low limit of detection (0.06 μM), and high specificity and storage stability. Finally, the innovative new UiO-66-NN-φ(OH)2 @ERGO/GC was applied to actual tap waters containing Cr 6+ and exhibited a wide recovery range that traditional ICP-AES validated. Graphical abstract: Image 1 Highlights: The homogenous 100 nm octahedral morphology UiO-66-NH2 MOF was prepared. The UiO-66-NN-φ(OH)2 /ERGO revealed high surface coverage of 6.63 × 10 −10  mol cm −2 . Brønsted acidities of Zr-η3 -OH and linker–OH group pKa measured as 3.32 and 4.40. The UiO-66-NN-φ(OH)2 @ERGO/GC able to sense wide range Cr 6+ (0.062–962 μM). This electrode revealed high sensitivity (0.211 μA μM −1 )), and low LOD (0.06 μM).